The Many Applications of Engineered Bacteriophages-An Overview - Bryan Gibb; Paul Hyman; Christine L. Schneider (MDPI AG, 2021)
Since their independent discovery by Frederick Twort in 1915 and Felix d'Herelle in 1917, bacteriophages have captured the attention of scientists for more than a century. They are the most abundant organisms on the planet, often outnumbering their bacterial hosts by tenfold in a given environment, and they constitute a vast reservoir of unexplored genetic information. The increased prevalence of antibiotic resistant pathogens has renewed interest in the use of naturally obtained phages to combat bacterial infections, aka phage therapy. The development of tools to modify phages, genetically or chemically, combined with their structural flexibility, cargo capacity, ease of propagation, and overall safety in humans has opened the door to a myriad of applications. This review article will introduce readers to many of the varied and ingenious ways in which researchers are modifying phages to move them well beyond their innate ability to target and kill bacteria.